The Works of Ukrainian Philosophers - Jevdokimenka, Vladimiras; Ničik, V. (Problemos, 1969)
Professional philosophy in the Ukraine originates from the 16th century. The development of philosophical knowledge is closely linked with the successive transition from the ideas of early humanism to idealistic systems, then to the enlightenment, revolutionary democratism, and, finally, to Marxism. At present Ukrainian philosophers work in the main on the study of Lenin’s theoretical legacy, objective laws governing the transition of the Soviet society from socialism to communism. Among other topics are theory of knowledge, and logic of scientific investigations, the history of philosophical and sociological thought in the Ukraine, and the methods of concrete sociological investigations.